Improving the cyclability of solid polymer electrolyte with porous V2O5 nanotube filler. (August 2022) - Feng, Tianshi; Hu, Yubing; Xu, Lei; Huang, Jinqiu; Hu, Sibo; Zhang, Lifeng; Luo, Langli
Abstract: Being the key component of all-solid-state batteries, solid-state electrolytes, especially solid polymer electrolytes (SPEs) are gaining increasing momentum toward large-scale fabrication owing to their excellent processability and compatibility with electrodes. However, relatively low ionic conductivity and electrochemical instability limit their applications. In this work, porous V2 O5 nanotubes (VNTs) were prepared by the electrospinning method and used as the filler for polyvinylidene fluoride (PVDF)-based SPEs. At 60 °C, the ionic conductivity of the SPE can achieve as high as 1.10 × 10 −2  S/cm while maintaining at 2.2 × 10 −3  S/cm at room temperature (RT) with improved mechanical properties. The Li symmetric cell exhibits a stable charge/discharge cycling of more than 2500 h. The asymmetric battery coupled with LiFePO4 achieved more than 300 cycles at a 0.1 C rate with a 95.3% capacity retention, and more than 300 times at 0.5 C when coupled with NCM811 with a 70% capacity retention, both at RT. The improved cyclability is attributed to the fine dispersion of VNT fillers and the alteration of PVDF crystalline fragmentation and bond chemistry induced by V2 O5, both of which lead to a fast and stable Li diffusion in the composite polymer electrolyte. Graphical abstract: Image 1 Highlights: Porous V2 O5 nanotubes are incorporated in PVDF to fabricate a composite polymer electrolyte for solid-state Li battery. The Li-ion conductivity of CPE reaches 2.2×10 −3 S/cm at room temperature with a stable cycling in symmetrical cell. The asymmetric cell coupled with LiFePO4 achieved > 300 cycles at a 0.1 C rate with a 95.3% capacity retention at RT. The structural and chemistry brought by VNT enables the fast ion-conduction with improved mechanical properties of CPEs.